Pengembangan Kelompok Kerja Menggunakan Model Open-System - Bahrul Ulumsyah; Muhammad Nur Syuhada (Journal of Economics and Management Scienties, 2023)
Group development is needed to provide support for achieving organizational goals. This includes efforts to understand and develop working groups. The purpose of group development is to ensure that the team works consistently, so as to produce optimal performance to achieve company targets. This studys uses a group-level Open System as an effort to understand and carry out group development. The subject of this study is part of the Human Capital Division at PT BM, namely the Organizational Developmen Unit with team members and environmental conditions. The data collection method used is interviews with all team members, team work environment observation, and document study of group performance profile. Data analysis is carried out by integrating findings that have been categorized based on the Open-System model qualitatively. The findings of this study indicate that the Open-System model is able to provide a structured description of the condition and performance of the Organizational Development Unit. The main problem condition obtained is that the group work target is not yet optimal. The intervention used to respond to the group assessment result is a measurable division of labor module, and become material for evaluating group performance on a small or large scale. So this research is expected to help the development of group performance optimally.